IoT-Based Air Quality Device for Smart Pollution Monitoring - Azahar, Mohd Azrol; Zainal, Mohd Shamian; Mohd Shah, Nor Shahidah; Md Nor, Danial; Hamzah, Shipun Anuar; Mohamed, Masnani (Progress in Engineering Application and Technology, 2020)
IoT-based Air Quality Device for Smart Pollution monitoring is built to replace traditional way of air quality monitoring methods of broadcasting the information to the public. This project proposes the IoT and Wireless Sensor Network (WSN)-based air quality monitoring system. The system must adopt the standard Air Pollution Index (API) and use the MQ135 gas sensor to detect multiple air gas concentrations. The device can connect to the internet using NodeMCU ESP8266 Wi-Fi module to store data collected in a cloud-based system. The data 00will be shown on any mobile device using the Blynk framework in the form of line graph visualization. The program will use social media to pass on air pollution data to some region when that area hits the unhealthy level of air pollution.